Converter Kit Technology Commercialization Strategy as A Solution for The Acceleration of The Electric Motor Vehicle Program - Sayyidah Maulidatul Afraah; Almira Husnun Nurhana Yasmono; Winanda Dyah Utari; Wahyudi Sutopo; Muhammad Hisjam (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
In Indonesia, motorcycle ownership is more than other motorized vehicles. However, the more motorbikes are used, the more vehicle emissions are released. So we need transportation solutions that are more environmentally friendly and energy efficient such as electric motorbikes which can be obtained with a converter kit by still utilizing existing conventional motorbike parts as provided by PT. A B C. However, many challenges were encountered in the commercialization of the converter kit from PT ABC, such as limited and uncertain suppliers, limited introduction to the market, and unpreparedness of Human Resources in product management. This study aims to analyze the constraints on the commercialization process of converter kit products as a basis for designing supply chain engineering proposals and appropriate business engineering. Based on the analysis of TRL and Goldsmith, it shows that the product is at TRL 8 or has fulfilled the requirements, but still has various obstacles. Based on the SWOT analysis, the company still has several shortcomings due to limited market interest, marketing strategies implemented, and price volatility. The results show that there is a business strategy design using the Business Model Canvas method to accelerate technology commercialization, one of which is through the expansion of existing partnership and marketing systems.